Static and dynamic bearing performances of hybrid gas dynamic bearings. (August 2021) - Zhang, Chuanbing; Ao, Hongrui; Jiang, Hongyuan
Abstract: Hybrid gas dynamic bearings (HGDBs) are designed to improve the viscous damping and stiffness of conventional gas foil bearings (GFBs). A static load-carrying capacity model coupling the rarefied gas effect, the roughness effect and the gas leakage effect is developed. The solution formula of maximum eccentricity ratio Ɛ max is established and the static load-carrying capacity that covers the whole interval [0, Ɛ max ] is analyzed. The dynamic analytical method of dynamic coefficients is proposed. Results show that the coupling of the rarefied gas effect, the roughness effect and the gas leakage effect decreases the static load-carrying capacity. The dynamic coefficients from dynamic sliding bearing model are smaller than those analysis results based on fixed sliding bearing model. Highlights: A static load-carrying capacity model with consideration of gas rarefaction effect, surface roughness effect and gas leakage effect is developed. The static load -carrying capacity throughout the whole interval [0, Ɛ max ] is analyzed. The dynamic performances of HGDBs are analyzed by using the partial derivative method.